Intramedullary Nailing of Proximal Tibia Fractures in Semi-extended Position Using Suprapatellar Approach: Results and Outcomes - Kumar Rohit; Vikas Verma (Journal of Orthopedics, Traumatology and Rehabilitation)
Aims and Objectives: This study aimed to evaluate the functional results and clinicoradiological outcomes of extra-articular closed proximal third tibia fractures managed by suprapatellar nailing in semi-extended position with a minimum follow-up of 12 months. Materials and Methods: In our prospective study, 15 cases of extra-articular closed proximal third tibia fractures admitted between January 2019 to December 2020, treated with intramedullary nailing through suprapatellar approach, were included. The patients were followed up regularly at 2 weeks, 6 weeks, 3 months, 6 months, 12 months, and every 6 months thereafter. The clinical outcome was analyzed using the Lower Extremity Functional Scale (LEFS) at 12 months’ follow-up visit. The radiological outcomes were analyzed by evaluating the radiographs for fracture union and alignment. Results: Fifteen patients having proximal third tibia fracture fulfilling the inclusion and exclusion criteria were included in the study. Patients had an average age of 34 years (24–55 years). The average follow-up period was 14 months (12–18 months) after the index procedure. The average time for radiological union was 6 months (range: 4–12 months). Two patients had procurvatum malalignment of >10°. We did not have significant rotational or varus/valgus malalignment or limb length discrepancy of >1 cm in our study. The average LEFS score at the 12 months’ follow-up was 88% (median: 90%; range: 80%–98%). Conclusion: We recommend the use of intramedullary suprapatellar nailing for fixation of proximal third tibial fractures. Suprapatellar nailing has inherent advantages of patient positioning for perfect nail entry and placement. When performed following the established surgical principles and techniques and proper patient and implant selection, it provides excellent clinicoradiological outcome with less complications as compared to other fixation methods for such fractures. There is also absence of anterior knee pain which is very common in the standard infrapatellar approach due to which its use could be extended for nailing of all types of tibia fractures.